The equation you have given is z^4 - 3z^2 + 2 = 0. Here you can replace z^2 = x to get a quadratic equation in x which can be solved.

z^4 - 3z^2 + 2 = 0

=> x^2 - 3x + 2 = 0

=> x^2 - 2x...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The equation you have given is z^4 - 3z^2 + 2 = 0. Here you can replace z^2 = x to get a quadratic equation in x which can be solved.

z^4 - 3z^2 + 2 = 0

=> x^2 - 3x + 2 = 0

=> x^2 - 2x - x + 2 = 0

=> x(x - 2) - 1(x - 2) = 0

=> (x - 1)(x - 2) = 0

So we have x = 1 and x = 2

As x = z^2

z^2 = 1 and z^2 = 2

z = -1 and z = +1 and z = +sqrt 2 and - sqrt 2

**The roots of the equation are -1 , 1 , sqrt 2 and -sqrt 2**